Exosomes in the Repair of Bone Defects: Next-Generation Therapeutic Tools for the Treatment of Nonunion. (4th August 2019) - Lu, Jian; Wang, Qi-Yang; Sheng, Jia-Gen
Abstract : Nonunion with bone defects, a common complication after long bone fracture, is a major challenge for orthopaedic surgeons worldwide because of the high incidence rate and difficulties in achieving successful treatment. Bone defects are the main complications of nonunion. The conventional biological treatments for nonunion with bone defects involve the use of autologous bone grafts or bone graft substitutes and cell-based therapy. Traditional nonunion treatments have always been associated with safety issues and various other complications. Bone grafts have limited autologous cancellous bone and there is a risk of infection. Additionally, problems with bone graft substitutes, including rejection and stimulation of bone formation, have been noted, and the health of the stem cell niche is a major consideration in cell-based therapy. In recent years, researchers have found that exosomes can be used to deliver functional RNA and mediate cell-to-cell communication, suggesting that exosomes may repair bone defects by regulating cells and cytokines involved in bone metabolism. In this review, we highlight the possible relationships between risk factors for nonunion and exosomes. Additionally, we discuss the roles of exosomes in bone metabolism and bone regeneration.